Contrast-enhanced fat-suppressed FLAIR for the characterization of leptomeningeal inflammation in optic neuritis - Pino-Lopez, Luis; Wenz, Holger; Böhme, Johannes; Maros, Máté E.; Schlichtenbrede, Frank; Groden, Christoph; Förster, Alex (Multiple sclerosis journal, 2019)
BACKGROUND: Leptomeningeal contrast enhancement on fluid-attenuated inversion recovery (FLAIR) images has been reported in patients with multiple sclerosis and interpreted as a biomarker of inflammation. In this study, we sought to evaluate this phenomenon in patients with optic neuritis (ON). - METHODS: A total of 42 patients with suspected ON were included in this prospective study and underwent a dedicated study magnetic resonance imaging (MRI) protocol including native and contrast-enhanced fat-suppressed thin-section axial and coronal FLAIR images on an 1.5 T magnetic resonance (MR) system. - RESULTS: After diagnostic workup, 34 patients with final diagnosis of ON were analyzed in detail. On contrast-enhanced fat-suppressed FLAIR images, 25 (73.5%) patients with ON demonstrated perioptic leptomeningeal enhancement, and in 3 (8.8%) patients, this was even the only pathological MRI finding. In comparison, patients with perioptic leptomeningeal enhancement on contrast-enhanced fat-suppressed FLAIR images had a higher prevalence of additional hyperintense brain lesions ( p = 0.022) as well as cerebrospinal fluid (CSF)-specific oligoclonal bands ( p = 0.013) than patients without. - CONCLUSION: Perioptic leptomeningeal contrast enhancement on fat-suppressed FLAIR images is a novel marker in ON and possibly reflects a leptomeningeal inflammatory process preceding or accompanying ON. Thin-section contrast-enhanced fat-suppressed FLAIR images might be a useful addition in MRI protocols for patients with suspected ON.